Effect of various mineral additives on the state of excretory renal function and the level of glycemia in rats in experimental alloxan diabetes mellitus - O. A. Nazarenko; O. A. Gromova (LLC "Publisher OKI", 2018)
On this study presents the results of the use of mineral additives salsamenteria of hypocol, selenopyran and Magne-Вб on alloxan model of diabetes in rats. A significant hypoglycemic effect of Magne B6 and selenopyran. It is revealed that all connections, especially hypocol and selenopyran have a beneficial effect on the excretory function of the kidneys in alloxan diabetes: reduce the severity of polyuria, glycosuria, and proteinuria (hypocol) and creatinine concentration in the blood (hypocol and selenopyran).